Web messaging among young people in online services: A descriptive mixed-methods study - Metsäranta Kiki; Anttila Minna; Pajamäki Tatjana; Holappa Heidi; Välimäki Maritta (SAGE PUBLICATIONS LTD, 2022)
Objective: To describe web messaging patterns and the content of web messages among young people in a Finnish national online service.
Methods: A descriptive mixed-method was used. The data consisted of text-based web messaging communication between young people and a counsellor in a nationwide online service between 1 January and 31 December 2018. Web messaging patterns were analysed using descriptive statistics. The content of the messages was analysed with thematic analysis and qualitative results were presented. In addition, the factors associated with messaging patterns and content were analysed.
Results: A total of 1941 messages were sent by 1354 young people. Most of them were between 12 and 17 years old and females. Less than one-fifth of young people had multiple two-way discussions with counsellor. The total period of two-way discussions and the number of words in each message varied widely. The number of words was lower in messages sent by males. The content of the messages was divided into three main themes: interpersonal relationships and environment (Social relationships), oneself (Construction of self), and health-related problems and support received from professionals (Health and wellbeing). The young people's messages mostly contained topics related to the main theme of 'Social environment'.
Conclusion: Most young people sent one message only. Messages ranged from simple, single messages to complex texts describing the daily life of young people. Girls were more active in messaging, and they wrote longer texts.